Determinants of Audit Quality: Empirical Evidence of Auditor Reputation, Audit Committee, Audit Fee, and Firm Sizes in Indonesian Financial Institutions (2020-2024) - Fitriyana, Saodah Dhona; Inayati, Nur Isna; Amir, Amir; Setyadi, Edi Joko (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2026)
This study looks at how auditor reputation, audit committee involvement, audit fee, and firm size affect audit quality in financial institutions listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. This study uses a quantitative method with secondary data obtained through the purposive sampling technique, resulting in 185 samples. The findings show that auditor reputation and audit fees do not have a meaningful impact on audit quality. On the other hand, audit committees and larger company sizes are linked to lower audit quality, suggesting that having an audit committee or being a bigger company doesn’t automatically mean better audit oversight. These results highlight the importance of improving corporate governance and making sure that the supervisory role is effective to enhance audit quality in the financial industry.